Illness perceptions and their relation to physical activity in children and adolescents with hemophilia. Issue 1 (1st January 2020) - Bérubé, Sarah; Amesse, Claudine; Sultan, Serge
ABSTRACT: Background: Hemophilia is a rare bleeding disorder in which illness perceptions have seldom been studied. Illness perceptions are important in predicting patients' behavior. Due to the risk of bleeding and joint damage, healthcare professionals often discourage some physical activities. Those restrictions can be difficult to follow for pediatric patients. This study investigates the relationship between illness perceptions, physical activity behavior, and intentions amongst this population. Methods: Twenty-four 6–18-year-old patients with severe hemophilia completed the Brief Illness Perception Questionnaire. A questionnaire assessing their level of physical activity and intentions toward safe and higher-risk physical activity was also administered. Clinical and socio-demographic data were collected. Associations were studied using hierarchical clustering of physical activity patterns, and Mann–Whitney U comparisons between clusters. Results: Perceptions ranged from slightly to moderately threatening, and 20–30% of participants had highly threatening perceptions on Consequences, Identity, Concern, and Emotional response. The subgroup who engaged in more high-risk physical activity and had stronger intentions to engage in this type of activity also held more concerns and perceived more symptoms. Conclusion: Patients at risk of non-adherence to recommendations concerning physical activity have more threatening illness beliefs that could be addressed during specific interventions or routine appointments. Addressing illness beliefs could be an element to behavior change. Strong emotional responses to hemophilia also stresses the need for psychosocial support strategies.